Single Neuroform Atlas stent: a reliable approach for treating complex wide-neck bifurcated aneurysms - Ahn, Hong Suk; Jeon, Hong Jun; Cho, Byung Moon; Park, Se Hyuck (Frontiers in Neurology, 2024)
Background: Treating wide-neck bifurcated cerebral aneurysms (WNBAs) using various techniques and new devices has shown favorable outcomes. However, endovascular coiling can be technically challenging when the aneurysm neck is incorporated into the parent vessel. Furthermore, although recent research has reported favorable outcomes of Neuroform Atlas stent (NAS)-assisted coiling, broad inclusion criteria have hampered precise evaluations of their effectiveness and safety for treating complex WNBAs. Therefore, this study evaluated whether the use of a single NAS is a safe and effective approach for treating complex WNBAs. Methods: We treated 76 complex WNBAs (unruptured, n = 49; ruptured, n = 27) using single NAS-assisted coil embolization and retrospectively analyzed the clinical and angiographic outcomes. Results: In a cohort of 68 patients (mean age, 58.3 ± 11.6 years; males n = 20, 29.4%; females, n = 48, 70.6%), 76 stents were successfully delivered to the target aneurysms, yielding a technical success rate of 98.6%. Complete occlusion was evident in 59 (77.6%) of 76 aneurysms, with neck remnants found in 16 (21.1%) and partial occlusion in 1 (1.3%). Treatment-related morbidities comprised one branch occlusion and one parenchymal hemorrhage. However, no new neurological symptoms of unruptured aneurysms were evident at discharge. The outcomes of 20 of the 27 ruptured aneurysms were favorable (Glasgow Outcome Scale scores of 4 or 5) at the final follow-up assessment (mean 12.2 [6–29] months]), except for one initial subarachnoid hemorrhage. Post-treatment angiography revealed complete occlusion in 89.1%, neck remnants in 7.8%, and incomplete occlusion in 3.1% of the aneurysms. Approximately 88.2% of the patients were assessed at least once by follow-up diagnostic or magnetic resonance angiography (mean, 12.5 ± 4.3 [range, 6–29] months), with five (7.8%) minor and two (3.1%) major recurrences. Conclusions: A single NAS is safe and effective for treating WNBAs incorporated into parent vessels.